THE VOCAL OF CREATIVE WORK OF ACTRESSES AT THEATRES OF HALYCHYNA (the end of the XIXth – the beginning of the XXth century) - Кукуруза, Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The research concerns the stage performance of the actors of the Galychyna theatrical troupes in the late 19th and early 20th centuries. In particular, it was madeanattempt to distinguish the musical aspect of their activity in performances, to determine the level of vocal skill in conjunction with the actor's. This is due to the synthetic repertoire of the period. The theater was not limited to dramatic performances (with singing) and light genres (vaudeville, operetta), but began to represent such a complex musical and dramatic genre as an opera. Consequently,the acting profession demanded versatility, which consists of the equal ability to play dramaticroleprofessionally, as well as to perform a vocal part.